2019
DOI: 10.1016/j.earlhumdev.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and cognition in preschool-age children with congenital gastrointestinal anomalies

Abstract: Background: Children with congenital gastrointestinal anomalies (CGIAs) experience multiple stressors while hospitalized in neonatal intensive care units during an essential time of growth and development. Early stress and inadequate nutrition are linked to altered growth patterns and later neurodevelopmental delays. In other at-risk populations, improved fat-free mass (FFM) accretion is associated with improved cognitive outcomes. Objective: To determine if body composition is associated with cognitive functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
(63 reference statements)
0
13
0
Order By: Relevance
“…Early stress and inadequate nutrition in infancy are linked to altered growth patterns (66, 67) and later neurodevelopmental delays (68, 69). It was shown that children with congenital gastrointestinal anomalies have similar growth and body composition to their peers (70). However, like pre-term-born children (71, 72), higher fat-free mass (but not fat mass) later in life is associated with higher cognitive test scores in children with congenital gastrointestinal anomalies (70).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early stress and inadequate nutrition in infancy are linked to altered growth patterns (66, 67) and later neurodevelopmental delays (68, 69). It was shown that children with congenital gastrointestinal anomalies have similar growth and body composition to their peers (70). However, like pre-term-born children (71, 72), higher fat-free mass (but not fat mass) later in life is associated with higher cognitive test scores in children with congenital gastrointestinal anomalies (70).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that children with congenital gastrointestinal anomalies have similar growth and body composition to their peers (70). However, like pre-term-born children (71, 72), higher fat-free mass (but not fat mass) later in life is associated with higher cognitive test scores in children with congenital gastrointestinal anomalies (70). Authors in the latter study concluded that closer tracking of body composition and interventions aimed at increasing fat-free mass may improve long-term outcomes in this population.…”
Section: Discussionmentioning
confidence: 99%
“…16,28 In a study by Plummer et al, in preschool age children with congenital GI anomalies, a greater amount of fat-free mass was associated with higher test scores. 10 However, there are concerns that early and rapid catch-up growth, particularly in premature infants and infants with intrauterine growth restriction, may increase the risk for later obesity and associated metabolic complications. 29 We recognize our study's limitations.…”
Section: Discussionmentioning
confidence: 99%
“…However, these infants are at high risk for growth failure. [1][2][3][4][5][6][7][8][9][10] These infants have prolonged stays in the neonatal intensive care unit due to feeding intolerance, intestinal surgeries, necrotizing enterocolitis, and sepsis. Moreover, these infants are often born prematurely and at risk for intestinal failure.…”
mentioning
confidence: 99%
See 1 more Smart Citation